Molecular identification of fungi and the types of toxins produced from contaminated corn grain in Satui, Tanah Bumbu, South Kalimantan, Indonesia - Salamiah Salamiah; Mariana Mariana; Yusriadi Marsuni; Muhammad Pramudi Indar; Muslimin Sepe; Lyswiana Aphrodyanti; Saipul Abbas (Universitas Lampung, 2025)
Fungal contamination in stored corn grain not only reduces grain quality but alsoposes risks to animal and human health due to mycotoxin production. This study highlights the importance of early detection and identification of fungal pathogens in corn as a key aspect of plant protection and postharvest management, as well as the need to determine the types and concentrations of toxins produced. Corn samples were collected from a storage warehouse in Satui Village, Kota Baru Regency, South Kalimantan. Fungal isolation was conducted at the Phytopathology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Lambung Mangkurat. PCR analysis and gene sequencing were performed at the Genetics Sciences Laboratory, Jakarta, while toxin type and content analyses were carried out at the Animal Husbandry Laboratory, Universitas Gadjah Mada, Yogyakarta. From 11 microbial isolates obtained from corn grain, only one fungal species was identified, namely Aspergillus flavus. This species was found to produce 8.00 ppb of aflatoxin, which remains below the established safety thresholds of 15 ppb for B1 and 20 ppb for total aflatoxins.